Implementasi program literasi kesehatan dalam penanganan stunting di Desa Tambak Kalisogo - Afrizal, Arrasyidin Diva; Rodiyah, Isnaini (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
The importance of health in preventing stunting requires solutions that involve the community so that the problem of stunting becomes a shared responsibility. For this reason, the implementation of the program through health literacy is present to fix the high number of stunting cases in Tambak Kalisogo Village. This study uses a qualitative approach. Data collection techniques were carried out through direct observation at the Kalisogo pond village office. Interview technique with the village secretary. The documentation section contains village profiles. The research data analysis technique used an interactive model with four stages, namely data collection, data condensation, data presentation and drawing conclusions. Where the variables of power, interests and strategies involved in implementing the policy already involve village health cadres who are responsible for village health. The second variable is the Characteristics of the Tambak Kalisogo Village Institution consisting of 848 families, totaling 2,468 people, with details of 1,229 male residents and 1,239 female residents. The third variable is the level of compliance with the response from the program implementers of the Prosperous Child Village who are considered to be quite enthusiastic.